Ortaöğretim Öğrencilerinin Tarih Kavramına İlişkin Sahip Oldukları Metaforlar / Secondary School Students’ Metaphors about the History Concept - Candan, Ahmet Sait; Öztaş, Sezai (Journal of History Culture and Art Research, 2017)
Abstract A metaphor is a figure of speech that refers to one thing by mentioning another thing via comparison, fictionalizing and expression. This study is revealing, in terms of metaphor concept, what the perceptions of the secondary school students with relate to “History” term are. Accordingly, comments of 160 students who are educating in secondary schools in Karabük city center are referred. In this research, the secondary school students’ perceptions about “History” term are tried to be determined via metaphors. The obtained data were analyzed with content analysis method by using the phenomenological pattern in terms of qualitative research method. As a result of this analysis, it has been revealed that metaphor is an effective factor in determining and expressing the perceptions of the secondary education students about “History” term. Öz Metafor bir şeyi başka bir şey ile benzetmeye, kurgulamaya, anlatmaya yarayan mecazlardır. Bu çalışma ortaöğretim öğrencilerinin “Tarih” kavramına ilişkin algılarının neler olduğunu metaforlar bağlamında ortaya koymaya yöneliktir. Bu doğrultuda Karabük il merkezinde bulunan ortaöğretim okullarında öğrenim gören 160 öğrencinin görüşlerine başvurulmuştur. Araştırmada çalışma grubundaki öğrencilerin “Tarih” kavramına yönelik algıları metaforlar üzerinden belirlenmeye çalışılmıştır. Elde edilen veriler, nitel araştırma yöntemi bağlamında olgubilim deseni kullanılarak içerik analizi tekniği ile analiz edilmiştir. Bu analiz sonucunda, ortaöğretim öğrencilerinin “Tarih” kavramına ilişkin sahip oldukları algıları belirlemede ve açıklamada metaforların etkin bir araç olduğu ortaya çıkmıştır.